2019
DOI: 10.1371/journal.pntd.0007447
|View full text |Cite
|
Sign up to set email alerts
|

Proposed multidimensional framework for understanding Chagas disease healthcare barriers in the United States

Abstract: BackgroundChagas disease (CD) affects over 300,000 people in the United States, but fewer than 1% have been diagnosed and less than 0.3% have received etiological treatment. This is a significant public health concern because untreated CD can produce fatal complications. What factors prevent people with CD from accessing diagnosis and treatment in a nation with one of the world’s most advanced healthcare systems?Methodology/Principal findingsThis analysis of barriers to diagnosis and treatment of CD in the US … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
46
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(52 citation statements)
references
References 87 publications
0
46
0
6
Order By: Relevance
“…Most cases that had completed follow-up by the end of the study had been cured of chronic S. stercoralis infection. In that regard, S. stercoralis serology is useful for post-treatment follow-up, as also observed by several research studies in immigrant populations in Europe and North America [ 39 , 44 ].…”
Section: Discussionmentioning
confidence: 74%
“…Most cases that had completed follow-up by the end of the study had been cured of chronic S. stercoralis infection. In that regard, S. stercoralis serology is useful for post-treatment follow-up, as also observed by several research studies in immigrant populations in Europe and North America [ 39 , 44 ].…”
Section: Discussionmentioning
confidence: 74%
“…According to Lynn, et al, they found that shared risk factors for transmission of Chagas disease in the United States were living in a rural area and/or a history of outdoor activities or work [15]. This leads us to conclude that healthcare providers serving populations in rural areas or underserved migrant population are a good starting point to target Chagas disease education efforts [12,[29][30][31].…”
Section: Introductionmentioning
confidence: 99%
“…As of 2017, only six states participate in surveillance and reporting of Chagas disease [12,31,32]. Educational materials on Chagas disease may be found online by several different sources and from the individual state health departments and the Centers for Disease Control and Prevention (CDC).…”
Section: Introductionmentioning
confidence: 99%
“…(15) This leads us to conclude that healthcare providers serving populations in rural areas or underserved migrant population are a good starting point to target Chagas disease education efforts. (12,(29)(30)(31) As of 2017, only six states participate in surveillance and reporting of Chagas disease. (12,31,32) Educational materials on Chagas disease may be found online by several different sources and from the individual state health departments and the Centers for Disease Control and Prevention (CDC).…”
Section: Introductionmentioning
confidence: 99%
“…(12,(29)(30)(31) As of 2017, only six states participate in surveillance and reporting of Chagas disease. (12,31,32) Educational materials on Chagas disease may be found online by several different sources and from the individual state health departments and the Centers for Disease Control and Prevention (CDC). Despite the availability of educational materials, a study on patient perspectives and access to Chagas disease in the United States emphasizes low awareness among providers and nonexistent health education campaigns as barriers to treatment.…”
Section: Introductionmentioning
confidence: 99%